The Relationship Between Balance And Leg Muscle Power With The Ability Of T Kick Speed In Pencak Athletes Youth Pledge Unit Bandar Lampung - Zaqi Arief Firmanto; Sudirman Husin; Candra Kurniawan; Lungit Wicaksono (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2023)
The purpose of this study was to determine the relationship between Balance and Leg Muscle Power with the ability of T kick speed in pencak silat athletes of Bandar Lampung youth oath unit. The method used in this study is quantitative method. With the research design consists of independent variables and dependent variables. Balance (X1), leg muscle power (X2), and kick speed ability T (Y), a sample of 17 pencak silat athletes from the Bandar Lampung youth oath unit. In this study, the data collection used survey methods with test and measurement techniques. The results showed that: (1) Balance has a significant relationship with the speed of the T kick, with the value of t count = 12.63 > ttable = 2.144. (2) Leg Muscle Power has a significant relationship with T kick speed, with t value = 21.291 > ttable = 2.144. (3) Limb Muscle Balance and Power have a significant relationship with T kick speed, with F count value = 120.273 > Ftable = 3.74. This study concluded that Balance and Power of Leg Muscles have a close relationship with the ability of T kick speed in pencak silat athletes of the Bandar Lampung youth oath unit.